Neoperla of unusual size from Vietnam (Plecoptera: Perlidae) - Stark, Bill P. (Illiesia, 2011)
Two large female specimens, representing a possible undescribed Vietnamese Neoperla species, are described under informal designation and compared to known Vietnamese congeners.
Keywords: entomology; Neoperla; Plecoptera; unusual size; Vietnam